Characterization of polyphenol oxidase activity in a range of forage ecotypes with different phenol substrates. A new insight for PPO and protein‐bound phenol evaluation. (19th September 2013) - Cabiddu, A.; Lee, M. R. F.; Decandia, M.; Molle, G.; Salis, L.; Vargiu, M.; Winters, A. L.
Abstract Plant phenols can influence utilization of forages by ruminants through binding with proteins either by complexing with oxidized phenols (products of polyphenol oxidase activity or formed in oxidizing conditions) or by hydrogen binding with tannins. These protein‐bound phenols (PBPs) affect rumen metabolism by inhibition of both proteolysis and lipolysis. The aim of this work was to assess the level of polyphenol oxidase (PPO) activity (determined with a range of diphenolic substrates), PBP content, and to identify the main source of variation in different forage ecotypes harvested at different phenological stages. PPO activity was strongly influenced by substrate type with a significant effect of forage ecotype. Forage ecotype and phenological stage also influenced PPO and PBP content. PPO showed a strong relationship with dry matter and phenol content of plants.